Analysis of farm profitability and the weighted upscaling system using the self-organizing map - Sulkava, Mika; Yli-Heikkilä, Maria; Latukka, Arto (Springer, 2013)
Profitability and other economic aspects of farming in Finland are analyzed using the self-organizing map. The analysis of profitability bookkeeping data reveals several interesting relationships between the monitored financial variables. A weight optimization system is presented for upscaling financial figures of the sample of profitability bookkeeping farms to the whole country level. The self-organizing map is also used to assess the performance of the weighting system. It is confirmed that the most important large and medium-sized enterprises are represented well by the sample. Furthermore, it seems that the utilized arable area is the key factor in guiding the weight optimization process. These findings may turn out to be useful in developing the sampling of bookkeeping farms in the future.
Keywords: MA; otokset; maatilat; kannattavuus; kirjanpito; optimointi; maatalous; farms; profitability; bookkeeping; agriculture; self-organizing map; optimization; constraint; neuroverkot